Parents’ Experiences of Nonsuicidal Self-Injury Among Adolescents and Young Adults - Kelada, L.; Whitlock, J.; Hasking, Penelope; Melvin, G. (Springer, 2016)
© 2016 Springer Science+Business Media New York. We assessed the impact of adolescent nonsuicidal self-injury (NSSI) on parents in two studies. In Study 1, 16 Australian parents of adolescents with a history of nonsuicidal self-injury responded to open-ended questions about their child’s nonsuicidal self-injury. Data from 10 of the adolescents were matched with parents’ responses regarding the nature and extent of nonsuicidal self-injury, revealing that parents underestimated the frequency of nonsuicidal self-injury, the age of onset, and the likelihood their child would continue to self-injure. In Study 2, 22 American parents of adolescents with a history of nonsuicidal self-injury participated in interviews about their experiences. Parents in both studies reported changes in the parent–adolescent relationship after self-injury, which posed challenges to the family unit. When professional help had been sought, experiences were largely negative. Results support further investigation into family-based interventions to equip parents with tools to better relate to, and communicate with, their adolescent following self-injury. Results also suggest that mental-health professionals and general practitioners may require further training for nonsuicidal self-injury.